2022
DOI: 10.1021/acs.joc.2c00037
|View full text |Cite
|
Sign up to set email alerts
|

Radical Acylalkylation of 1,3-Enynes To Access Allenic Ketones via N-Heterocyclic Carbene Organocatalysis

Abstract: An N-heterocyclic carbene organocatalytic 1,4-difunctionalization of 1,3-enynes was developed. This organocatalytic strategy was suitable for a broad spectrum of substrates to efficiently synthesize allenic ketones bearing diverse substituents. Preliminary mechanistic studies suggest a radical reaction pathway for this organocatalytic acylalkylation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 83 publications
0
19
0
Order By: Relevance
“…As disclosed in recent studies, they generally led to poor yields, including our stereoconvergent allenylation reaction (20-23) 50,[53][54][55] . Aliphatic aldehydes, substituted with diverse primary or secondary alkyl chains, participated efficiently in this 1,4functionalization of 1,3-enynes (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). However, moderate diastereoselectivities (5:1 dr to 10:1 dr) were generally observed in the cases of primary aliphatic aldehydes (24)(25)(26)(27)(28)(29), probably resulting from the reduced steric hindrance in comparison with secondary alkyl aldehydes (30)(31)(32)(33)(34)(35)(36)(37)(38)(39).…”
Section: Substrate Scopementioning
confidence: 99%
See 1 more Smart Citation
“…As disclosed in recent studies, they generally led to poor yields, including our stereoconvergent allenylation reaction (20-23) 50,[53][54][55] . Aliphatic aldehydes, substituted with diverse primary or secondary alkyl chains, participated efficiently in this 1,4functionalization of 1,3-enynes (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). However, moderate diastereoselectivities (5:1 dr to 10:1 dr) were generally observed in the cases of primary aliphatic aldehydes (24)(25)(26)(27)(28)(29), probably resulting from the reduced steric hindrance in comparison with secondary alkyl aldehydes (30)(31)(32)(33)(34)(35)(36)(37)(38)(39).…”
Section: Substrate Scopementioning
confidence: 99%
“…1a) 3 . On the other hand, the radical 1,4-functionalization of 1,3-enynes via allenyl or propargylic radicals has attracted much attention recently [20][21][22][23][24][25][26][27][28][29] , but only limited success has been achieved in their asymmetric versions. In 2020, the Bao and Zhang groups 30 , and Liu group 31 independently reported the elegant Cu-catalyzed enantioselective synthesis of chiral allenes via the radical 1,4-dicarbonization of 1,3-enynes.…”
mentioning
confidence: 99%
“…These methods show a wide scope with respect to the alkene acceptor, and styrenes, vinyl Along with alkenes, 1,3-enynes were also found to be potent radical acceptors that participate in analogous NHC-catalyzed three-component cross-couplings. In 2021, Du, 65 Huang, 66 and Li 67 independently demonstrated that perfluoroalkyl radicals regioselectively add to the terminal alkenyl moiety of the 1,3enyne to afford transient allenyl radicals, which can then be trapped by the cogenerated ketyl radicals to obtain tetrasubstituted allenyl ketones (Scheme 8).…”
Section: Set Oxidation Of Breslowmentioning
confidence: 99%
“…This transformation exhibited remarkable tolerance to diversified radical precursors, aliphatic and aromatic aldehydes and enyne substitution. Recently, Li's group developed the similar strategy with mainly 4‐aryl substituted 1,3‐enynes as the substrates [45] …”
Section: Organocatalyzed Reactions Involving Allenyl Radicalsmentioning
confidence: 99%